Nuevas citas del género Sticta (Schreb.) Ach. (Ascomycetes Lichens, Peltigeraceae, Lobarioidea) para Argentina - Rodríguez, María Pía (2023)
Fil: Rodríguez, María Pía. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Botánica del Nordeste; Argentina.